Star trek: prodigy. Season 1 [videorecording (DVD)] - Hageman, Kevin; Hageman, Dan (Paramount, 2023)
It follows the intergalactic adventures of six teenagers as they try to escape from their cruel past and look to the stars for hope and salvation aboard an abandoned Federation starship. These outcasts know nothing about the ship they have commandeered a first in the history of Star Trek but throughout their adventures together, they are introduced to Starfleet and the ideals it represents. Contains Episodes 1-10.